Responding to Theology Religionum in Christian Religious Education - Lasmaria Nami Simanungkalit; Bobby Kurnia Putrawan (Institut Agama Kristen Negeri Tarutung, 2021)
Lately, religion has become something scary and worrying. Religion in the hands of its followers often appears with a face full of violence and as if it has lost its friendliness. In recent years, there have been many conflicts, intolerance and violence in the name of religion and belief. Religious pluralism is not a reality that requires people to put each other down, belittle each other, or confuse one religion with another, but instead places it in a position of mutual respect, mutual recognition and cooperation. In order to eliminate the destructive aspects of religion and present its constructive side as a unifier, schools as institutions mandated to educate the nation's life must participate in providing an understanding of religion and must be able to create an environment that provides education. Opportunities for students to build harmonious social relationships between students of different religions. For this reason, an effort is needed in certain religious communities to reflect or think coherently about the new awareness as an effort to respond to this problem of pluralism. To address this matter, Religionum Theology as a branch of theology that discusses how Christianity responds to the reality of the existence of religious plurality outside itself, especially in Christian Religious Education.